Processos de gestão de pessoas na rede municipal de ensino de Santa Maria/RS - Souza, Simone Fréo de (2023)
This research work, from the Professional Master's Course, from the Postgraduate Program inPublic Policies and Educational Management at UFSM, addresses people management in thearea of Education. Its general objective is to understand the people management processes carried out in the Municipal Education Network of Santa Maria/RS, in order to contribute to therearticulation and qualification of the Personnel Staffing Plan. And for specific objectives it prioritizes: i) historicizing educational and school management policies and processes in con- junction with democratic management; ii) identify how people management processes take place in the Municipal Education Network of Santa Maria/RS; iii) recognize, from the perspec-tive of educational and school managers in the Municipal Education Network of Santa Maria/RS, the demands, challenges and possibilities related to people management processes;iv) build guiding parameters that contribute to the rearticulation and qualification of people management processes in the Municipal Education Network of Santa Maria/RS. Methodolog-ically, this is an involved research of a qualitative nature, which was carried out with managersfrom the Municipal Education Network of Santa Maria/RS (RME/SM), using documentary anal-ysis, mixed online questionnaire and semi-structured interview. The data constructed indicatesthat the research provided opportunities for dialogue and listening to managers, in which it waspossible to establish comparisons and reflections on the analyzed documents and bibliog- raphies, in order to establish approximations with the demands and resignifications of the pro-cesses related to the RME Staffing Plan /SM that, in the perception of managers, the processes are organized and well conducted, but need to be rearticulated and permanently qualified. Considering that this is a professional master's degree research, the aim was to contribute to the systematization of people management processes in the Municipal Education Network of Santa Maria/RS, culminating, therefore, with the shared elaboration of a “Booklet of technicalguidelines for the construction of the Staffing Plan for this Education Network”.